Production of cell wall degrading enzymes and antibiotic by Pseudomonads for assessing their biocontrol potential - CHALOTRA, RASHMI; MALLICK, S A; GUPTA, MONI; SHARMA, DEEPIKA; GUPTA, SACHIN (The Indian Journal of Agricultural Sciences, 2019)
A comprehensive study on bio-control efficacy of different Pseudomonas species was made in terms of cell wall degrading enzymes, viz. chitinase, lipase, protease and antibiotic 2, 4- diacetylphloroglucinol (2,4- DAPG) production abilities in respect to changing temperatures and pH. Observations revealed that all the isolates of Pseudomonas spp. under study produced all the three cell wall degrading enzymes and 2,4- DAPG significantly. However, the isolates PS-11 and PS-30 exhibited maximum enzyme producing abilities. Moreover, PS-11 could be considered to be the maximum heat tolerant among the isolates as it maintain remarkable sustainability even at 55° C in the ability to produce enzymes with minimum losses in activities 0.1026 to 0.718 in chitinase, 3.1167 to 2.1794 in lipase and 0.5827 to 0.4075 in protease activities due to rise of temperature from 45° C to 55° C. In pH variation studied at 35°C, it was observed that chitinase, lipase and protease production abilities of most of the isolates of Pseudomonas spp. were maximum at pH value of 6.5 and decreased on further lowering to 5.5 or rising to pH 8.5. PS-30 recorded the highest production of 2,4-DAPG (767.37 μg/ml) at 30° C and pH 6.5.